Basics of computed tomography (CT) - Kachelrieß, Marc (Henry Stewart Talks, 2010)
Technical basics of clinical X-ray CT, From single-slice to multi slice, The CT hardware, Mechanics, X-ray source and X-ray detector technology, Image reconstruction of circular, sequential and spiral CT, Specific applications, Dose reduction strategies
Reviewed at 2022/01/23